Identifying Coping Strategies in Parents of Children With Neurodevelopmental Disorders: A Qualitative Inquiry - Ma, James; Saadati , Seyed Alireza (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to explore and identify coping strategies employed by parents of children with neurodevelopmental disorders, focusing on emotional, social, practical, and resilience-based dimensions of adaptation. A qualitative research design was adopted, utilizing semi-structured interviews with 23 parents of children diagnosed with neurodevelopmental disorders residing in Canada. Participants were recruited purposively through support groups, clinical networks, and community organizations. Interviews, lasting between 45 and 90 minutes, were conducted either face-to-face or online, audio-recorded, and transcribed verbatim. Data collection continued until theoretical saturation was reached. NVivo 14 software supported data organization and thematic analysis, following Braun and Clarke’s six-phase framework. Credibility and trustworthiness were enhanced through peer debriefing, independent coding, reflexive memoing, and the use of thick description. Analysis revealed four overarching themes: (1) Emotional coping—including stress management, emotional expression, reframing, self-compassion, and hope maintenance; (2) Social support strategies—such as peer support, family involvement, professional guidance, online communities, and workplace flexibility; (3) Practical coping—involving structured routines, resource utilization, problem-solving, and information-seeking behaviors; and (4) Personal growth and resilience—comprising identity transformation, spiritual coping, meaning-making, empowerment through knowledge, and self-care practices. Illustrative quotations from participants highlighted how coping strategies were dynamically employed to navigate ongoing challenges and sustain parental well-being. Parents of children with neurodevelopmental disorders adopt multifaceted coping strategies that extend beyond stress relief to encompass resilience-building and personal growth. These findings underscore the importance of designing culturally and contextually relevant interventions that strengthen parental coping resources, enhance family adaptation, and improve overall quality of life.